The Correlation Between PBL (Project-Based Learning) and Learning Motivation in ELT Classes - Auliya Rahma Maziidah; Dian Novita Dewi (Journal of Educational Sciences, 2023)
In recent times, learners are required to have the skill of the 21st century, such as collaboration, critical thinking, communication, and technology used as the impact of a more digitized and globalized era. One of the teaching methods which equipped student’s skill needs is PBL (Project-Based Learning). PBL is also named the effective method to apply because students are asked to create their learning content as the implementation of student-centered learning. This teaching method is widely used at any educational level and could enhance students’ motivation. Thus, to determine the correlation between the PBL teaching method and students’ learning motivation, the researcher conducted a study of 67 students in 11th grade at SMA Panjura Malang that opts for a correlation method with a quantitative approach. The questionnaire was adopted and analyzed, it showed that there is a correlation between the PBL learning method and students’ learning motivation in ELT classes. The result was a medium positive relation which means that PBL could be an alternative recommended method to apply in ELT classes.